The role of newly industrialized economies in global value chains - Boddin, Dominik (Washington, DC, 2016)
"In light of increased vertical specialization and the dominance of trade in intermediates rather than final goods, this paper seeks to raise awareness of the limitations of traditional trade measures on a gross output basis. To do so, this paper uses the WIOD, a world input output table, as an alternative trade measure to analyze the role of six newly industrialized economies in global value chains. The differences between measures on a gross output basis and value added basis are striking. Export shares measured by both methods differed by more than 20 percent for some industries. These findings highlight the need for more sophisticated world input output data to form a better understanding of global trade dynamics and country interdependencies."